Development Strategy of Village Tourism Based on Green Economy in Denai Lama Village, Deli Serdang - Ilham Habibi Lubis; Maryam Batubara; Muhammad Arif (Asian Journal of Applied Business and Management, 2023)
This study identifies key strategies for developing Green Economy-based village tourism in Denai Lama Village, Deli Serdang. It assesses internal and external conditions and emphasizes crucial steps for focused development. Using qualitative methods like SWOT analysis and QSPM, five local SMEs and five experts responded to the questionnaire. SWOT analysis places strategies in Quadrant I, implying progressive use of strengths and opportunities. QSPM highlights showcasing authentic Nusantara art in Pasar Kamu as the top priority. This aims to attract both local and international tourists, establishing it as the village's unique attraction.